The synthesis of TiAlN composites by condensation of the different arc plasma flows - Taran, V.S.; Tereshin, V.I.; Timoshenko, A.I.; Chechel’nitskij, O.G.; Kryshtal’, A.P. (Вопросы атомной науки и техники, 2005)
Some properties of the arc-vapour deposited TiAlN films, obtained both – by condensation of the different and combined titanium and aluminium plasma flows, have been investigated. The different flows was provided by two arc evaporators with titanium and aluminium cathodes, at that, the aluminium plasma was passed through the curvilinear plasma filter. The combined titanium-aluminium plasma was generated by single evaporator with the alloyed TiAl cathodes, which have a volumetric content of aluminium 50 %. The growth rates, surface morphology and the Vickers hardness of the TiAlN films, obtained under the various conditions, have been analyzed. The comparative cutting tool trials with the cemented carbide drills, covered by TiN, TiCN and TiAlN were conducted. It is shown, that the TiAlN film compositions, condensed from different plasma flows with the filtering aluminium plasma, are more profitable and has much higher characteristics, than films, obtained from alloyed TiAl cathodes. Досліджено властивості композитів TiAlN одержаних із окремих і сполучених потоків титанової та алюмінієвої плазми. Генерування окремих потоків забезпечувалося двома вакуумно-дуговими випаровувачами з титановим і алюмінієвим катодами, причому, алюмінієва плазма проходила через криволінійний плазмовий фільтр, де очищалася від парiв і макрочасток. Сполучений потік титан-алюмінієвої плазми створювався одним випаровувачем з використанням сплавних катодів TiAl, що мiстили 50 об'ємних % алюмінію. Визначено стiйкiстнi характеристики твердосплавного інструменту, зміцненого покриттями TiAlN. Показано, що композити TiAlN, конденсовані з окремих потоків з фiльтрацiєю алюмінієвої плазми, більш рентабельні і мають більш високі характеристики, нiж покриття, одержанi з використанням сплавних катодів. Исследованы свойства композитов TiAlN полученных конденсацией раздельных и совмещенных потоков титановой и алюминиевой плазмы. Генерирование раздельных потоков обеспечивалось двумя вакуумно- The quantity of holes, N 5 10 15 Fig. 3. The quantity of holes, perforated in tempered steel (HRC 52) with a drills of Mitsubishi Carbide: – uncoated –TiN-coated coated; –TiCN –TiAlN non- filtering –TiAlN with Al-plasma filtering дуговыми испарителями с титановым и алюминиевым катодами, причем, алюминиевая плазма проходила через криволинейный плазменный фильтр, где очищалась от паров и макрочастиц. Совмещенный поток титан-алюминиевой плазмы создавался одним испарителем с использованием сплавных катодов TiAl с объемным содержанием алюминия 50%. Исследованы стойкостные характеристики твердосплавного инструмента, упрочненного покрытиями TiAlN. Показано, что композиты TiAlN, осажденные из раздельных потоков с сепарацией алюминиевой плазмы, более рентабельны и обладают более высокими характеристиками, чем покрытия, полученные с использованием сплавных катодов.